2017
DOI: 10.5539/elt.v11n1p21
|View full text |Cite
|
Sign up to set email alerts
|

Learning from ELLs’ Perspectives: Mismatch between ELL and Teacher Perspectives on ELL Learning Experiences

Abstract: Situated within Activity Theory, this study investigates and compares ELLs' perspectives on their own learning and their teachers' perspectives on their own learning experiences. The predilection carried by this study is that there is a significant value in attending to and understanding how ELL students make meaning of their learning circumstances and compare that to teachers' perspectives on their students' learning. This study also assumes that allowing student voice and perspective to be heard in school is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Moreover, this finding may support to the previous research of Thongma ( 2013) and Buangern and colleagues (2008), finding that Lao teachers of English in secondary schools lack various instructional techniques, and teachers cannot understand the learning characteristics among students, that includes lacking applying a suitable teaching approach to students (Sengsouliya et al, 2015). The present study has found the same result as of past researches (Akbarzadeh & Fatemipour, 2014;Asba, 2014;Fang, 2012;Ghada, Rima, Nola, & Mona, 2011;Karabuga, 2015;Peacock, 2001;Shim & Shur, 2018), indicating that mismatches do exist in English teaching-learning process. The present study found that teachers are likely to have a preference towards visual teaching style, which is well consistent with that of Asba (2014).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Moreover, this finding may support to the previous research of Thongma ( 2013) and Buangern and colleagues (2008), finding that Lao teachers of English in secondary schools lack various instructional techniques, and teachers cannot understand the learning characteristics among students, that includes lacking applying a suitable teaching approach to students (Sengsouliya et al, 2015). The present study has found the same result as of past researches (Akbarzadeh & Fatemipour, 2014;Asba, 2014;Fang, 2012;Ghada, Rima, Nola, & Mona, 2011;Karabuga, 2015;Peacock, 2001;Shim & Shur, 2018), indicating that mismatches do exist in English teaching-learning process. The present study found that teachers are likely to have a preference towards visual teaching style, which is well consistent with that of Asba (2014).…”
Section: Discussionsupporting
confidence: 89%
“…Through reviewing a wide range of literature, Asba and colleagues (2014) found that mismatches in styles between teacher and students do exist in educational settings. In previous studies (Akbarzadeh & Fatemipour, 2014;Asba et al, 2014;Fang, 2012;Ghada, Rima, Nola, & Mona, 2011;Karabuga, 2015;Shim & Shur, 2018), the findings have proved that mismatches in styles between teachers and students occur. For instance, Fang (2012) explored whether or not mismatches exist in teacher's teaching styles and students' learning styles in China.…”
Section: Mismatches In Teacher Teaching and Student Learning Stylesmentioning
confidence: 87%
See 2 more Smart Citations
“…Teachers in the differentiated classroom, however, strive to base instruction on student interests, needs, and readiness and use various teaching processes and instructional approaches to ensure that students reach their potential (Abbati, 2012;Strassman, 2004;Wu & Chang, 2014). Shim and Shur (2017) pointed out that teachers not only needed to find the distinctions between ELLs and non-ELLs, but also realize ELL students' performance was on a spectrum, showing significantly different performance levels among groups or clusters. In particular, for the students who have special needs, one of the strategies is to form groups of students and to provide task differentiation within the various group participants.…”
Section: Applying Differentiated Pedagogy In the Mathematics Classroommentioning
confidence: 99%